ETYMOLOGY AND ECOLOGY : CAN ETYMOLOGY BE AN AID IN ECOLOGICAL EDUCATION? THE CASE OF THE SARDINIAN WORD MITSA. - Marinella Lörinczi (European Scientific Journal, ESJ, 2014)
In Sardinia, hilly areas cover 67.9% of its land. Its climate is prevalently Mediterranean, with prolonged summer drought and mild winters. Of the more than thirty thousand springs found in Sardinia, most fall into the category of small. Anthropization of springs, which is common in settled areas and in their vicinity, has occurred even at the springs scattered over the countryside, in places known only to the experts. In the Sardinian language we find many different names for springs: mitsa is typical of the central southern area. I will reconsider the discussion of the etymology of mitsa (Guarnerio, Wagner, Mensching). Mensching rejects the prestigious etymology of Wagner who argued for a Punic origin of this word. His final hypothesis is that mitsa may derive from an endocentric Latin/Romance syntagm: TERRA MITIA. I will support this hypothesis on the basis of the cognitive motivation of the meaning. As direct knowledge of the object and its environment are in some cases of fundamental importance in understanding the origin of nouns and changes in their meanings, this kind of research can be embodied in the discipline that from the ‗90s onwards is referred to as ecolinguistics.